A qualitative exploration of contraceptive use and discontinuation among women with an unmet need for modern contraception in Kenya - Susan Ontiri; Lilian Mutea; Violet Naanyu; Mark Kabue; Regien Biesma; Jelle Stekelenburg (BMC, 2021)
Abstract Background Addressing the unmet need for modern contraception underpins the goal of all family planning and contraception programs. Contraceptive discontinuation among those in need of a method hinders the attainment of the fertility desires of women, which may result in unintended pregnancies. This paper presents experiences of contraceptive use, reasons for discontinuation, and future intentions to use modern contraceptives. Methods Qualitative data were collected in two rural counties in Kenya in 2019 from women with unmet need for contraception who were former modern contraceptive users. Additional data was collected from male partners of some of the women interviewed. In-depth interviews and focus group discussions explored previous experience with contraceptive use, reasons for discontinuation, and future intentionality to use. Following data collection, digitally recorded data were transcribed verbatim, translated, and coded using thematic analysis through an inductive approach. Results Use of modern contraception to prevent pregnancy and plan for family size was a strong motivator for uptake of contraceptives. The contraceptive methods used were mainly sourced from public health facilities though adolescents got them from the private sector. Reasons for discontinued use included side effects, method failure, peer influence, gender-based violence due to covert use of contraceptives, and failure within the health system. Five reasons were provided for those not willing to use in the future: fear of side effects, cost of contraceptive services, family conflicts over the use of modern contraceptives, reduced need, and a shift to traditional methods. Conclusion This study expands the literature by examining reasons for contraceptive discontinuation and future intentionality to use among women in need of contraception. The results underscore the need for family planning interventions that incorporate quality of care in service provision to address contraceptive discontinuation. Engaging men and other social influencers in family planning programs and services will help garner support for contraception, rather than focusing exclusively on women. The results of this study can inform implementation of family planning programs in Kenya and beyond to ensure they address the concerns of former modern contraception users.